Finance and employment formalization: Evidence from Mexico's ENIGH, 2000-2016 - Santiago Bazdresch (Banco de México, 2018)
We study the relationship between financial constraints and employment formalization by exploiting heterogeneity in the industry-level degree of financial dependence, in the spirit of Rajan and Zingales (1998). This dependence, and variation in aggregate credit, lets us measure industry-level financial slack, and estimate its effects on employment formality. We find formality among young workers increases, which is consistent with a model of informal firms that grow and formalize with financial resources, thus becoming more productive. However, we find that financial slack, apparently, decreases formality among older, experienced workers, which is consistent with a model of capital-constrained formal employees that turn into entrepreneurs when financial conditions improve. Descriptive statistics on formality, as well as regression estimates conditioning by age and schooling provide a detailed map of the differential effects of finance on formality.
Keywords: G2; J46; O11; O12; O16; 330; Self-Employment; Entrepreneurship; Financial Constraints; Employment Formality; Financial Dependence